An inexpensive and worldwide available digital image analysis technique for histological fibrosis quantification in chronic hepatitis C. Issue 3 (24th July 2013) - Campos, C. F. F.; Paiva, D. D.; Perazzo, H.; Moreira, P. S.; Areco, L. F. F.; Terra, C.; Perez, R.; Figueiredo, F. A. F.
Summary Hepatic fibrosis staging is based on semiquantitative scores. Digital imaging analysis (DIA) appears more accurate because fibrosis is quantified in a continuous scale. However, high cost, lack of standardization and worldwide unavailability restrict its use in clinical practice. We developed an inexpensive and widely available DIA technique for fibrosis quantification in hepatitis C, and here, we evaluate its reproducibility and correlation with semiquantitative scores, and determine the fibrosis percentage associated with septal fibrosis and cirrhosis. 282 needle biopsies staged by Ishak and METAVIR scores were included. Images of trichrome‐stained sections were captured and processed using Adobe® Photoshop® CS3 and Adobe® Bridge® softwares. The percentage of fibrosis (fibrosis index) was determined by the ratio between the fibrosis area and the total sample area, expressed in pixels calculated in an automated way. An excellent correlation between DIA fibrosis index and Ishak and METAVIR scores was observed (Spearman's r = 0.95 and 0.92; P < 0.001, respectively). Excellent intra‐observer reproducibility was observed in a randomly chosen subset of 39 biopsies with an intraclass correlation index of 0.99 (95% CI, 0.95–0.99). The best cut‐offs associated with septal fibrosis and cirrhosis were 6% (AUROC 0.97, 95% CI, 0.95–0.99) and 27% (AUROC 1.0, 95% CI, 0.99–1), respectively. This new DIA technique had high correlation with semiquantitative scores in hepatitis C. This method is reproducible, inexpensive and available worldwide allowing its use in clinical practice. The incorporation of DIA technique provides a more complete evaluation of fibrosis adding the quantification to architectural patterns.